Selection criteria of methodologies of software development - Tinoco Gómez, Oscar (2010)
In the last two decades, on these software development methodologies has been engaged in intense debate between two currents. On the one hand, the so-called traditional methods, focusing on process control, with rigorous monitoring of the activities involved in them. On the other hand, agile methods, focusing on human factors in collaboration and customer participation in the development process and a relentless increase in software with very short iterations. The article presents a proposal, in the midst of this debate, to select a software development methodology.